Coping Stress on Single Mothers in Sidoarjo Regency: Mengatasi Stres pada Janda di Kabupaten Sidoarjo - Prayitno, Dio Lambang; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2023)
The family is the main and most responsible institution in society in ensuring the social welfare and biological preservation of human children, because it is in the family that human children are born, and the death of a spouse is one of the most important life events and can trigger stress. When a woman finally becomes a single mother, they are generally in a condition that is vulnerable to physical and psychological disorders. The purpose of this study was to analyze the description of coping stress on single mothers, sources of stress on single mothers and analyze the factors that influence the selection of coping stress on single mothers in Buduran sub-district, Sidoarjo district. This research method uses qualitative research methods, the unit of analysis in this study is the conceptual understanding of the topic of coping stress and single mother, the subject of this research is a single mother who is in Wadungasih Village, Buduran District, Sidoarjo Regency. Based on the results of the study, it can be said that the stress coping chosen by single mothers in Buduran sub-district, Sidoarjo Regency is more focused on emotional-focused coping (avoidance of running away, keeping distance, positive reappraisal, self-control and emotional social support) especially single mothers chosen. the longer one. Meanwhile, problem focused coping (confrontive coping) was chosen by subjects who had just become single mothers. Sources of stress experienced by single mothers in Buduran sub-district, Sidoarjo district are the economy, work, taking care of children, and negative views of the people around them. What factors influence the choice of coping with stress in single mothers in Buduran sub-district, Sidoarjo district, namely physical health, problem solving skills, social skills, and social support.